Assessment of wall deflection and strut forces for excavations in clay - T. Sathiyaa (2015)
Over the years, there has been a surge in demand for development and infrastructural needs, and as a result, more and more excavations have been carried out. This is especially true in Singapore, where population influx and land scarcity is becoming truly concerning. Excavation works are pivotal in maintaining our surging development and infrastructural demands. Due to such constraints, there is an obvious need to excavate deeper underground. Having a braced system as support prevents the collapse of the excavated soil during work, allowing deep excavation. In this project, the finite element program, Plaxis 2D, was used to fulfil the two objectives of assessing maximum lateral wall deflection and strut forces, for braced excavation in soft clay. There were numerous cases simulated on the Plaxis 2D software, and in the different cases, several parameters were varied. These parameters included wall stiffness, the excavated depth to the hard stratum, embedment length of the wall and the excavated width. The result reveals that maximum lateral wall deflection increases when the depth of excavation increases, and when the excavation width enlarges. In contrast, the findings show that maximum lateral wall deflection decreases when wall stiffness increases, and when wall embedment depth increases. Moreover, the results also indicate that strut forces increase as wall stiffness increases, and when depth of excavation increases. Strut forces decline when wall embedment depth increases and when excavation width increases. In most cases, it was observed that the 4th strut experienced the highest compressive force and the 1st strut occasionally is in tension which in part is due to the kickback of the wall during construction.